The Use of Code-Switching in English Foreign Language Classroom of SMKN 2 Sinjai - Bahrun, St Rahmaniah; Aminah, Sitti (Universitas Islam Ahmad Dahlan (UIAD), 2020)
This research aims at finding out (1) the types of code-switching used by the teachers in theforeign language classroom, (2) functions of code switching used by the teachers in the foreignlanguage classroom, and (3) the implication of code-switching on TEFL. The research employeddescriptive qualitative research design. The subjects were three English teachers of SMKN 2 Sinjai.All of them used Buginese language in their daily life but in class they used Indonesian language asmother tongue and English language as target language. The researcher findings that there are fivetypes of code-switching that used by the teachers in teaching and learning process. Those were intersentential code-switching, intra-sentential code-switching, extra-sentential or tag switching,establishing continuity with the previous speaker and emblematic. The data had shown that there weresix functions’ code-switching. Those were topic switch, reiteration, checking the studentsunderstanding, for instruction, grammar translation and explanation, inserting humor and expressemotion. The implication of code-switching on TELF was very useful because it can be used as amethod or strategy in explaining English materials, motivating the students to speak specially for lowlevel students, analyzing problem and encourage them to pay attention when the teacher explainingmaterial.